PENINGKATAN HASIL BELAJAR SOAL CERITA PERKALIAN PEMBAGIAN PECAHAN MELALUI STRATEGI PEMBELAJARAN BERBASIS MASALAH DI KELAS V SDN 28 KOTA PAYAKUMBUH - Nofandi, Rinaldo; Ahmad, Syafri; Farida, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
The purpose of this study was to describe improvement in learning outcomes story matter multiplication division a fraction throug strategy probelm based learning in class v sdn 28  payakumbuh city. This research is a classroom action research (PTK), using a qualitative and quantitative approach. The results showed an increase in: (a) Learning Planning in the first cycle obtained an average of 87,49% (B) increased in the second cycle to 92.85% (SB), (b) Learning Implementation aspects of the teacher the first cycle obtained an average the average is 80,84% (B) increased in the second cycle to 93.34% (SB) and the Learning Implementation aspects of the first cycle students get an average of 72,65% (C) increased in the second cycle to 87.50% (SB), (c) Learning outcomes of students in cycle I obtained an average of 77.28 (C) increased in the second cycle to 91.56 (SB). From the results of the study it be concluded using problem based learning strategy can improves the science learning outcomes student on multiplication division a fraction.Keywords : learning outcomes, problem based